Permasalahan Yang Dihadapi Guru Dalam Pembelajaran Anak Berkebutuhan Khusus Tunagrahita Di UPTD SDN Gunungsekar 2 Sampang, Madura - Gilang Achmad Marzuki; Nova Estu Harsiwi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The purpose of this research is to delve deeper into the issues faced by teachers in implementing inclusive schooling at UPTD SDN Gunungsekar 2 Sampang. The researcher employs a qualitative approach, gathering data through interviews, observations, and documentation, which are then analyzed using qualitative analysis methods. The findings of this study reveal several challenges encountered by teachers in inclusive education, including lack of parental knowledge, difficulty for students in grasping the material, and limited variation in the use of teaching methods and media. Efforts undertaken by the school to address these challenges include conducting enjoyable learning processes using various methods and media, involving students with special needs in all learning activities, providing additional time for these students, and offering guidance or seminars to both special education teachers and regular classroom teachers.